2019
DOI: 10.1101/825828
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nix induced mitochondrial fission, mitophagy, and myocyte insulin resistance are abrogated by PKA phosphorylation

Abstract: Lipotoxicity is a form of cellular stress caused by the accumulation of lipids resulting in mitochondrial dysfunction and insulin resistance in muscle. Previously, we demonstrated that the mitophagy receptor Nix is responsive to lipotoxicity and accumulates in response to diacylglycerols induced by high-fat (HF) feeding. In addition, previous studies have implicated autophagy and mitophagy in muscle insulin sensitivity. To provide a better understanding of these observations, we undertook gene expression array… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 70 publications
(107 reference statements)
0
0
0
Order By: Relevance
“…Studies have shown that the ratio of BCL-2/Bax is higher in drug-resistant cells than in sensitive cells (75). YWHAB, as an anti-apoptotic protein, can also cause insulin resistance in cells by affecting mitochondrial polarization (76). Our research suggests that YWHAB may play an essential role in affecting cell drug sensitivity, providing insights to further study the mechanisms of drug resistance and develop new therapeutic strategies.…”
Section: Discussionmentioning
confidence: 65%
“…Studies have shown that the ratio of BCL-2/Bax is higher in drug-resistant cells than in sensitive cells (75). YWHAB, as an anti-apoptotic protein, can also cause insulin resistance in cells by affecting mitochondrial polarization (76). Our research suggests that YWHAB may play an essential role in affecting cell drug sensitivity, providing insights to further study the mechanisms of drug resistance and develop new therapeutic strategies.…”
Section: Discussionmentioning
confidence: 65%